The Pseudomonas aeruginosa AlgZR two-component system coordinates multiple phenotypes - Okkotsu, Yuta; Little, Alexander S.; Schurr, Michael J. (Frontiers in Cellular and Infection Microbiology, 2014)
Pseudomonas aeruginosa is an opportunistic pathogen that causes a multitude of infections. These infections can occur at almost any site in the body and are usually associated with a breach of the innate immune system. One of the prominent sites where P. aeruginosa causes chronic infections is within the lungs of cystic fibrosis patients. P. aeruginosa uses two-component systems that sense environmental changes to differentially express virulence factors that cause both acute and chronic infections. The P. aeruginosa AlgZR two component system is one of its global regulatory systems that affects the organism’s fitness in a broad manner. This two-component system is absolutely required for two P. aeruginosa phenotypes: twitching motility and alginate production, indicating its importance in both chronic and acute infections. Additionally, global transcriptome analyses indicate that it regulates the expression of many different genes, including those associated with quorum sensing, type IV pili, type III secretion system, anaerobic metabolism, cyanide and rhamnolipid production. This review examines the complex AlgZR regulatory network, what is known about the structure and function of each protein, and how it relates to the organism’s ability to cause infections.